1997
DOI: 10.1002/(sici)1097-0339(199704)16:4<336::aid-dc6>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytology of pleuropulmonary blastoma: Case report and review of the literature

Abstract: This report describes the fine‐needle aspiration (FNA) cytology of a case of pleuropulmonary blastoma in a 3‐yr‐9‐mo‐old male. Pleuropulmonary blastoma is considered by most authors to be distinct from pulmonary blastoma and is a rare malignant tumor of the intrathoracic cavity. FNA smears were cellular with numerous small ovoid to spindled cells with oval to elliptical nuclei exhibiting finely granular chromatin and inconspicuous nucleoli. The cytoplasm was scant and cosinophilic with indistinct borders. Foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…In another study, Kim et al described the cytologic findings of 17 sarcomas that were metastatic to the lung 13. The remaining reports were limited to individual case studies and small series 14–36. In the current study, we reported the findings of a series of 61 spindle cell lesions of the lung evaluated by FNA, with reference to the differential diagnosis, potential pitfalls, and appropriate use of ancillary studies.…”
mentioning
confidence: 99%
“…In another study, Kim et al described the cytologic findings of 17 sarcomas that were metastatic to the lung 13. The remaining reports were limited to individual case studies and small series 14–36. In the current study, we reported the findings of a series of 61 spindle cell lesions of the lung evaluated by FNA, with reference to the differential diagnosis, potential pitfalls, and appropriate use of ancillary studies.…”
mentioning
confidence: 99%
“…If PPB recurs in an individual patient, the type has often progressed to more advanced disease 4,10 . The diagnosis is made only on histologic evaluation of the excised mass; however, fine-needle aspiration cytology has been used to diagnose it 13,14,15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is made only on histologic evaluation of the excised mass. However, ®ne-needle aspiration cytology has been used to diagnose it [21,22]. Complete excision may not be possible if the tumour has invaded adjacent vital mediastinal structures, in which case partial excision or biopsy is carried out followed by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%